Non-farm employment, natural resource extraction, and poverty: evidence from household data for rural Vietnam - Manh Hung Do; Trung Thanh Nguyen; George Halkos; Ulrike Grote (Environment, Development and Sustainability, 2022)
Natural resources are important in sustaining the livelihoods of rural households and the environment. However, over-exploitation is causing an alarming depletion of natural resources in many developing countries. At the same time, rapid economic growth has created non-farm employment opportunities for local people. In this context, examining the interrelationship between non-farm employment and natural resource extraction provides useful information for reducing resource extraction and improving rural households' welfare. In this study, we use a dataset of 1780 identical households from three survey waves undertaken in 2010, 2013, and 2016 in Vietnam to (i) identify the determinants of rural households' participation in non-farm activities, (ii) examine the interrelationship between non-farm employment and natural resource extraction, and (iii) investigate the impact of non-farm employment on rural households' welfare. The findings from pooled sample estimations reveal that (i) cable internet at home and rural road quality positively affect households' decisions to participate in non-farm employment; (ii) non-farm income and income from natural resource extraction have a negative association; and (iii) non-farm income significantly contributes to poverty reduction in both relative and absolute terms. Our findings suggest that improved provision of non-farm opportunities and increased investment in infrastructure and telecommunication are needed to improve rural households' welfare and consequently reduce their natural resource exploitation.
Keywords: Q57; Q12; R20; 330; Rural livelihood; Heckman selection model; Simultaneous regression model; Instrumental variable